Profil Imunohistokimia Antioksidan Copper, Zinc-Superoxide Dismutase (Cu, Zn, -SOD) pada Ginjal Tikus Perinatal dan Neonatal - Tutik Wresdiyati; I Ketut Mudite Adnyane; Silvia Arin Prabandari; Sofiawati Sofiawati (Universitas Atma Jaya Yogyakarta, 2004)
The aim of the research was to observe the profile of intracellular antioxidant, especially copper, zinc-superoxide dismutase (Cu, Zn-SOD) in the kidney of perinatal and postnatal rats immunohistochemically. A total of twuelve Wistar rats were used for this research and they were divided into four groups that are 18 days (Fe18) and 20 days old fetus (Fe20), one day (N1) and three days neonatus (N3). There are three rats in each groups. Kidney from each group were taken and processed for routin paraffin embedding methods. The tissues sections were observed with Hematoxylin-eosin (HE) and immunohistochemical technique for Cu, Zn-SOD. Cu,Zn-SOD in the kidney were observed qualitatively in medulla, glomerulus dan cytoplasm of tubuli renalis proximalis and tubuli renalis distails, as well as quantitatively in the nucleus of tubuli renalis cells. The results showed that Cu, Zn-SOD increased in the kidney of perinatal rats, 20 days old fetus (Fe20), then it decreased in the tissues of the one days neonatus (N1), then were increased again in the kidney of three days neonatus (N3) group rats.